Conceptualizing reflection in experience-based workplace learning. Issue 4 (8th August 2017) - Lundgren, Henriette; Bang, April; Justice, Sean B.; Marsick, Victoria J.; Poell, Rob F.; Yorks, Lyle; Clark, Molly; Sung, SeoYoon
ABSTRACT: This paper seeks to understand key dimensions of reflection in experience-based workplace learning for research being collaboratively undertaken by scholars in Dutch and US research institutions. We systematically explore and compare Tara Fenwick's analysis of five perspectives on cognition to distinguish among constructivist, psychoanalytic, situative, critical-cultural, and enactivist perspectives on reflection. Our aim is to examine how to conceptualize reflection so that one or more perspectives can complement our understanding of learning through experience at work. We position reflection not only from a practical but also from a theoretical perspective that moves beyond the individual focus of the constructivist perspective. Fenwick's five perspectives are described in terms of whether and how reflection is utilized, key activities in the process of reflection, relative focus on the individual and/or the context, triggers for reflection, role of power and positionality, role of emotions, and reflection outcomes. We conclude that adding other lenses to the dominant constructivist perspective helps expand our understanding of reflection as well as identify and attend to other tools, people, and factors in the work situation that influence reflection processes and learning outcomes. The paper closes with a discussion of promising new approaches that have emerged since Fenwick's analysis.